Low-carbon landscape management system / Nur Hanim Ilias ... [et al.] - Ilias, Nur Hanim; Mansor, Azran; Abdul Malek, Nurhayati; Wan Omar, Wan Rabiah; Bahaluddin, Azrul (2024)
A low-carbon landscape management system has been developed to assist landscape architects or park managers in managing landscapes with a low-carbon footprint. Effective low-carbon landscape management is crucial for meeting the world agenda in Sustainable Development Goals (SDG) and national low-carbon targets. This innovation consists of three phases of data integration: Phase 1 -planning, Phase 2 – implementation and maintenance, and Phase 3 – low-carbon management. The main objective of this system is to offer complete and integrated data to enhance the value of low-carbon landscapes for plants. This includes providing relevant information such as i) Plant inventory details like plant species, location, size, source, and quantity; ii) Assessing the health and fitness of plants to determine their value; and iii) Calculating the carbon footprint of landscape management to understand plants' contribution to carbon mitigation. Landscape development is vital in mitigating climate change and promoting environmental sustainability by evaluating carbon-saving potential and implementing appropriate landscape development.